The Role of Financial Literacy in Enhancing SME Access to Financial Services, Growth and Sustainable Development in Zimbabwe - Taurayi Stephen NYAGOPE; Owen Simon NYAGOPE (International Journal of Environmental, Sustainability, and Social Science, 2024)
This study sought to determine the Role of Financial Literacy on Accessibility, Growth and Sustainability in Small and Medium Enterprises Zimbabwe. It underlines the role of SMEs in generating employment and Gross Domestic Product during a challenging financial environment where high interest rates, strict collateral requirements, as well as lack of specialized products for SMEs leave much to be desired. Financial literacy was also given priority in the research as crucial for SME owners and managers so that they can apply financial services efficiently not just understanding them but doing such things borrowing, budgets, investment, and risk management. The main value of the study was in its ability to guide policymakers, financial institutions, and educators about how a good training on financial literacy could improve SMEs’ performance and growth. The research emphasized the gap in growth among SMEs despite government action, addressing any existing gaps relative to a study done on the impact of financial literacy as compared with performances by various enterprises. The methodology involved a positivist research philosophy, an explanatory research design and a case study approach which utilised both quantitative and qualitative data analysis. This study was set geographically as SMEs in Harare with the data collected through questionnaires and secondary sources such as Reserve Bank of Zimbabwe and World Bank. Upon data analysis, there was a strong relationship between financial literacy and SME performance. In conclusion, the study established that financial literacy played a critical role in determining whether SMEs were successful and sustainable in Zimbabwe.